DIGITAL TRANSFORMATION OF THE INSURANCE INDUSTRY: THE POTENTIAL OF INSURANCE TECHNOLOGY (INSURTECH) IN INDONESIA - Susanto, Ari (Transpublika Publisher, 2022)
The insurance industry cannot be separated from the demands to keep up with the times and carry out digital transformation of its business. Digital transformation in the insurance industry has driven the emergence of insurance technology (InsurTech). The development of insuretech in Indonesia is quite fast and will continue to grow with the emergence of various digital insurance service providers such as PasarPolis, E-Bancassurance, Fuse and so on. Insurtech can be utilized throughout the lifecycle of insurance products including pre-contract, product development, post-contract, back office operations and in risk control. The digitalization of technology in Indonesia has driven the development of InsurTech's business. Key players in this industry include PasarPolis, Qoala and Simas Insurtech. InsurTech's high potential in Indonesia is not only supported by the development of InsurTech start-ups, but also due to low insurance penetration. The challenges that arise for InsurTech are mainly related to the current regulations that do not yet specifically discuss InsurTech.